“Our Culture is a Product of Active Word”: A Poetic Inquiry into Immigrants’ Experiences with Writing in a Host Language - Kalan, Amir (Art/Research International, 2024)
With a focus on the intersection of creative writing and research, this article reports findings from a poetic inquiry project conducted within an undergraduate writing seminar to help pre-service teachers make sense of immigrants’ experiences with writing in a new culture and language. A group of undergraduate students in Ohio were invited to make found poetry based on interview data from conversations with immigrants about writing in English as their learned language. Adopting Bourdieu’s theories, the research reveals the dynamics shaping the writing culture in North America. The students’ found poems reflect a sensitivity to the societal, political, and ideological foundations of writing. Importantly, the poems recognize writing as a tool for immigrants’ identity negotiation and highlight how rhetorical control can be used for cultural assimilation. In response, some of the students’ found poems advocate for rhetorical complexity and co-constructions of new cultural futures by immigrants and their hosts.